Clinical significance of prediabetes, undiagnosed diabetes and diagnosed diabetes on critical outcomes in COVID‐19: Integrative analysis from the Japan COVID‐19 task force. Issue 1 (26th September 2022) - Fukushima, Takahiro; Chubachi, Shotaro; Namkoong, Ho; Asakura, Takanori; Tanaka, Hiromu; Lee, Ho; Azekawa, Shuhei; Okada, Yukinori; Koike, Ryuji; Kimura, Akinori; Imoto, Seiya; Miyano, Satoru; et al.
Abstract: Aim: Diabetes mellitus (DM) is a known risk factor for severe coronavirus disease 2019 (COVID‐19), but the clinical impact of undiagnosed diabetes and prediabetes in COVID‐19 are unclear particularly in Japan. We clarify the difference in clinical characteristics, including age, sex, body mass index and co‐morbidities, laboratory findings and critical outcomes, in a large Japanese COVID‐19 cohort without diabetes, with prediabetes, undiagnosed diabetes and diagnosed diabetes, and to identify associated risk factors. Materials and Methods: This multicentre, retrospective cohort study used the Japan COVID‐19 Task Force database, which included data on 2430 hospitalized COVID‐19 patients from over 70 hospitals from February 2020 to October 2021. The prevalence of prediabetes, undiagnosed diabetes and diagnosed diabetes were estimated based on HbA1c levels or a clinical diabetes history. Critical outcomes were defined as the use of high‐flow oxygen, invasive positive‐pressure ventilation or extracorporeal membrane oxygenation, or death during hospitalization. Results: Prediabetes, undiagnosed diabetes and diagnosed diabetes were observed in 40.9%, 10.0% and 23.0%, respectively. Similar to diagnosed diabetes, prediabetes and undiagnosed diabetes were risk factors for critical COVID‐19 outcomes (adjusted odds ratio [aOR] [95% CI]: 2.13 [1.31‐3.48] and 4.00 [2.19‐7.28], respectively). HbA1c was associated with COVID‐19 severity in prediabetes patients (aOR [95% CI]: 11.2 [3.49‐36.3]), but not other groups. Conclusions: We documented the clinical characteristics and outcomes of Japanese COVID‐19 patients according to HbA1c levels or diabetes co‐morbidity. As well as undiagnosed and diagnosed diabetes, physicians should be aware of prediabetes related to COVID‐19 severity.